Struktur modal dan kepemilikkan asing terhadap agresivitas pajak perusahaan manufaktur di Indonesia - Junaidi, Ahmad; Harini, Ririn; Yuniarti, Rina; Sumarlan, Ahmad (Universitas Widya Mataram, 2023)
This study aims to determine the effect of capital structure and foreign ownership on corporate tax aggressiveness in food and beverage companies listed on the IDX. Tax aggressiveness is the dependent variable The independent variable, while foreign ownership is the independent variable. This type of research is quantitative with secondary data sources obtained from annual reports and financial reports on the Indonesia Stock Exchange. The population in this study is 30 food and beverage companies listed on the IDX for 2018-2020. The sample is 27 companies obtained by the purposive sampling method. Data were analyzed using SPSS software version 26. The result showed that capital structure has a negative and significant effect on tax aggressiveness and foreign ownership has a positive and significant impact on tax aggressiveness. To get better results, further research can add other variables, use companies other than manufacturing, and extend the research period.